Factor Analysis for Clustering and Estimating Fish Distribution Pattern in a Tropical Estuary in Southern Thailand - Saheem, Niwadee; Chesoh, Sarawuth; Lim, Apiradee (Agriculture and Natural Resources, 2015)
This study investigated the pattern of the fish standing crop using data on weight by month and sampling locations in the Na Thap River inSouthern Thailand. Samples of 28 different estuarine fish species were collected monthly at four different locations on the river from June 2005 to December 2012. Factor analysis was used to group the number of species and hence produced four interpretable factors:factor 1 was represented by a group of marine organisms, factors 2 and 3 represented mainly euryhaline species and factor 4 was a group of mesohaline species. The results indicated that all four fish groups reached maximum levels during February and March. The fish standing crop by weight for each factor was significantly associated with the month of the year. The results suggest that the fish standing crop was associated with a season.